AI’s role in improving community corrections - Pavon-Harr, Viveca (The journal of offender monitoring, 2021)
Community corrections has a mission that is as socially important as it is difficult. Yet, when broken down to its constituent parts, the mission revolves around just three seemingly straightforward components: investigating, understanding, and influencing human behavior for the betterment of society. Of course, human behavior is infinitely complex, and understanding it has vexed the greatest minds in every field, not just criminal justice. Fortunately, there are repeatable tasks related to the community corrections mission that can be facilitated by automation and improved through Artificial Intelligence (AI). This article examines the current state of AI technology, and the many useful applications of artificial intelligence to community corrections and the criminal justice system, including the application of machine-learning analytics to millions of documents including probation reports and court records; monitoring fidelity in the implementation of evidence-based rehabilitation; and identifying precursor behaviors among monitored offenders that might signal a potential violation or significant mental health problem.